Purgatori Dalam Katolik Dan Neraka Dalam Islam: Kajian Komparatif Atas Konsep Kehidupan Setelah Kematian - Siregar, Ilham Jaya Kusuma; Zulkarnaen, Zulkarnaen (Jayapangus Press, 2025)
The concept of purifying fire, whether in the form of Purgatory in Catholic teachings or Hell in Islam, is an important topic in the eschatological studies of both religions. Purgatory is understood as a temporary stage of purification for souls who die in a state of grace but still carry minor sins, while Hell in Islam is described as a place of eternal punishment for those who disbelieve or commit major sins. This study aims to compare the concepts of Purgatory and Hell from the perspectives of Catholicism and Islam, as well as to analyze the theological implications of both concepts. The research method employed is a literature review, involving the collection and analysis of data from various literary sources such as the Bible, the Qur’an, Hadith, and theological works. The results of the study indicate that although there are differences in emphasis and description, both concepts share the same purpose, which is to emphasize the importance of living a righteous life and obeying God. In Catholicism, Purgatory functions as a mechanism of purification before entering Heaven, while in Islam, Hell serves as a place of punishment and a warning for humanity. Both concepts also reflect divine justice and mercy in addressing human sin.